In-situ observations of single micro-particle impact bonding. (1st March 2018) - Hassani-Gangaraj, Mostafa; Veysset, David; Nelson, Keith A.; Schuh, Christopher A.
Abstract: We study supersonic impact of individual metallic microparticles on metallic substrates, that is, the unit process of materials buildup in cold spray coatings/additive manufacturing. We resolve the moment of impact bonding through real-time observations of single particle impacts with micron-scale and nanosecond-level resolution. We offer the first in-situ observation of a material-dependent threshold velocity, above which the particle undergoes an impact-induced jet-like material ejection and adheres to the substrate. We report direct measurements of critical velocities for structural metals, which unlike in nozzle experiments, are not affected by process-related complexities obscuring particles' kinetic and thermal histories. Graphical abstract: